The use of TIVA in a patient with Gilbert's syndrome. Issue 2 (31st July 2013) - McCawley, Declan
Summary: Gilbert's syndrome is a common condition due to an inherited disorder of hepatic bilirubin metabolism. This is a report of the anaesthetic management of the use of TIVA (total intravenous anaesthesia) for breast surgery under general anaesthesia. Perioperative goals are to minimise fasting and stress during the perioperative period, while avoiding hepatotoxic drugs and those which are exclusively metabolised by the liver.